ISG15–LFA1 interactions in latent HIV clearance: mechanistic implications in designing antiviral therapies - Koka, Prasad S.; Ramdass, Bharathi (Frontiers in Cell and Developmental Biology, 2024)
Interferon types-I/II (IFN-αβ/γ) secretions are well-established antiviral host defenses. The human immunodeficiency virus (HIV) particles are known to prevail following targeted cellular interferon secretion. CD4+ T-lymphocytes are the primary receptor targets for HIV entry, but the virus has been observed to hide (be latent) successfully in these cells through an alternate entry route via interactions with LFA1. HIV facilitates its post-entry latency-driven mode of hiding through these interactions to displace or inhibit ISG15 by forming the HIV1-LFA1 complex in lieu of ISG15-LFA1, which would at least transiently halt and bypass type-I IFN secretion. This could explain why the elimination of HIV from cellular hideouts is difficult. Hence, HIV clearance needs to be addressed to reverse its latency in LFA1+ T-lymphocytes and CD34+/CD133+ early progenitor stem cells. In the context of hematopoietic or endothelial stem-progenitor cells (HSPC/ESPC), we discuss the potential role of LFA1 in HIV permissiveness and latency in LFA1-CD34+/CD133+ versus LFA1+CD34+/CD133+ HSPCs/ESPCs. In HIV latency, the viral particles may remain engaged on the naïve-resting cells’ LFA1, which are then unable to accommodate the ISG15 molecules owing to conformational changes induced upon occupation by the virus at the ISG15-LFA1 binding or interaction sites through halting of the subsequent downstream type-II IFN secretion. Viral binding to LFA1, including its transfer through activated-naïve cell–cell contacts may be a key step that needs to be addressed to prevent “transient or partial” virus-induced shutdown of type-I IFN secretion. This process allows an alternate viral entry and hideout site via LFA1. The subsequent administration of recombinant ISG15 may ensure sufficient type I/II IFN release to promote, enhance, or sustain the innate immune responses. Thus, combination antiviral therapies could potentially include exogenous ISG15 to maintain or sustain biologically and clinically relevant ISG15-LFA1 interactions. In addition to alternating with co-challenges of PKC-pro-LRA-drug modulators, this is administered post (antiretroviral therapy) and continued with periodic ART until permanent elimination of viral resurgence and latency is achieved in patients with HIV/AIDS. This triple-combination drug regimen is expected to pave the path for systemic virus clearance in vivo.